INSPIRASI MODEL RAMBUT LAYER UNTUK TAMPILAN FRESH DAN MODERN - Anik Maghfiroh; Ifa Nurhayati; Salma Oktavina; Sakti Putri Prasetya; Maulida Firda Ayuningsih (JURNAL ILMIAH NUSANTARA, 2025)
Beauty trends, including hairstyles, continue to evolve with the times. One hairstyle that remains popular and relevant today is the layered haircut, which gives dimension, volume, and a more vibrant and modern look. This article aims to provide inspiration and an in-depth understanding of layered hair from an aesthetic and functional perspective. The method used is a literature review by analyzing scientific literature and beauty trends in the last five years The findings show that layer cuts not only enhance the visual appearance of the hair, but can also be adapted to various face shapes and hair types, supporting the modern concept of beauty that prioritizes simplicity and functionality. Various layer variations such as short, medium, long, and shaggy layers, as well as combinations with styling techniques such as flat iron, curling iron, blow in, and blow out, further enrich the versatility of the look. The implication of this article is that layer cuts can be an adaptive solution in the modern beauty world, offering a fresh, practical, and elegant look, as well as boosting individual confidence through proportional visual aesthetic adjustments.